(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
Today, the concept of innovation is entering every aspect. Everyone knows that this is happening in all aspects of the economy. Therefore, this article focuses on the definitions given to them, including some information about the concept of innovation, innovative technology, its essence and objects.